2012
DOI: 10.1099/mic.0.058610-0
|View full text |Cite
|
Sign up to set email alerts
|

A luminescent reporter evidences active expression of Ralstonia solanacearum type III secretion system genes throughout plant infection

Abstract: Although much is known about the signals that trigger transcription of virulence genes in plant pathogens, their prevalence and timing during infection are still unknown. In this work, we address these questions by analysing expression of the main pathogenicity determinants in the bacterial pathogen Ralstonia solanacearum. We set up a quantitative, non-invasive luminescent reporter to monitor in planta transcription from single promoters in the bacterial chromosome. We show that the new reporter provides a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 49 publications
5
87
1
Order By: Relevance
“…g 21 stem (Jacobs et al, 2012). A luminescent reporter fused to hrpB was used to confirm that hrpB was transcribed throughout plant infection, even at late stages, where cells proliferate and reach a high cell density (Monteiro et al, 2012). In this study, we demonstrated that hrpG expression was dramatically decreased in the leaves and in the xylem at high cell density, i.e.…”
Section: Discussionmentioning
confidence: 66%
“…g 21 stem (Jacobs et al, 2012). A luminescent reporter fused to hrpB was used to confirm that hrpB was transcribed throughout plant infection, even at late stages, where cells proliferate and reach a high cell density (Monteiro et al, 2012). In this study, we demonstrated that hrpG expression was dramatically decreased in the leaves and in the xylem at high cell density, i.e.…”
Section: Discussionmentioning
confidence: 66%
“…R. solanacearum was routinely grown at 30°C in rich B medium or Boucher's minimal medium (MM) supplemented with 20 mM L-glutamate (Sigma-Aldrich, St. Louis) as a carbon source (Boucher et al 1985;Monteiro et al 2012a). Tetracycline (at 10 and 5 g/ml in liquid cultures) and gentamicin (75 and 5 g/ml in liquid cultures) were used for selection in R. solanacearum.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…To prepare inocula, bacterial strains were grown overnight in liquid rich B medium (Boucher et al 1985;Monteiro et al 2012a) at 30°C with shaking at 200 rpm. Cells were pelleted by centrifugation, suspended in water, and spectrophotometrically adjusted to 10 7 CFU/ml.…”
Section: Plant Inoculation and Disease Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…The T3SS of R. solanacearum contributes greatly to pathogenesis, but hrp mutants retain the ability to invade tomato roots and systemically colonize the vascular system, although the population size of T3SS mutants in infected tissues was reduced by 10 to 1000 fold compared to wild-type strains [16,17]. Recently, in planta transcriptome study and qRT-PCR tests by Jacobs et al [18] and in planta expression study using green fluorescent protein reporter fusions by Monterio et al [19] found that the T3SS is still active even after R. solanacearum has taken over the xylem, suggesting that the T3SS is functional throughout disease. These results changed the wide spread view from in vitro studies that T3SS is only active at the first stage of infection and is not needed when bacteria reach high cell densities [20,21].…”
mentioning
confidence: 99%